The Dead Sea scrolls and the developmental composition of the Bible - Ulrich, Eugene, 1938- (Vetus Testamentum, Supplements, 2015)
Winner of the 2015 Choice Outstanding Academic Title Award Winner of the Frank Moore Cross Award for Best Book in Biblical Studies from ASOR Winner of the Biblical Archaeology Society 2017 Publication Award for Best Book Relating to the Hebrew Bible Eugene Ulrich presents in The Dead Sea Scrolls and the Developmental Composition of the Bible ( (also available as paperback) the comprehensive and synthesized picture he has gained as editor of many biblical scrolls. His earlier volume, The Biblical Qumran Scrolls , presented the evidence - the transcriptions and textual variants of all the biblical scrolls - and this volume explores the implications and significance of that evidence. The Bible has not changed, but modern knowledge of it certainly has changed. The ancient Scrolls have opened a window and shed light on a period in the history of the text's formation that had languished in darkness for two thousand years. They offer a parade of surprises that greatly enhance knowledge of how the scriptural texts developed through history.